2020
DOI: 10.3389/fcimb.2020.530160
|View full text |Cite
|
Sign up to set email alerts
|

Interactions Between Therapeutics for Metabolic Disease, Cardiovascular Risk Factors, and Gut Microbiota

Abstract: With improved standards of living, the incidence of multiple metabolic disorders has increased year by year, especially major risk factors for cardiovascular disease such as hyperglycemia and hyperlipidemia, continues to increase. Emerging epidemiological data and clinical trials have shown the additional protective effects of some metabolic therapy drugs against cardiovascular diseases. A series of studies have found that these drugs may work by modulating the composition of gut microbiota. In this review, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 174 publications
(194 reference statements)
0
18
0
Order By: Relevance
“…Decreased amounts in obesity and diabetic patients vs. healthy individuals; higher quantity is associated with improvement in cardiac metabolic parameters in obesity [122] Lactobacillales, Bacteroides and Prevotella…”
Section: Type Of Bacteria Descriptionmentioning
confidence: 99%
“…Decreased amounts in obesity and diabetic patients vs. healthy individuals; higher quantity is associated with improvement in cardiac metabolic parameters in obesity [122] Lactobacillales, Bacteroides and Prevotella…”
Section: Type Of Bacteria Descriptionmentioning
confidence: 99%
“…The main bacterial species in the gut, such as Lactobacillus and Bifidobacterium taxa, express the enzyme bile salt hydrolase (BSH), which deconjugates BAs from glycine and taurine [ 104 ]. According to research, intestinal inflammation [ 105 ], metabolic disorders such as diabetes [ 106 ], and cardiovascular disease [ 107 ] are pathologically determined by gut microorganisms and abundant BSH genes. Metabolite analysis of young stroke patients showed that their serum glycochenodeoxycholic acid (GCDCA) concentration was significantly higher than that of healthy controls [ 108 ].…”
Section: Mechanism Of the Interactions Between The Gut Microbiota And...mentioning
confidence: 99%
“…The gut microbiota is an important environmental factor and there is increasingly concrete evidence that the activity and composition of the gut microbiota are closely related to health. 52,53 The gut microbiota is hypothesized to participate in nutrient and energy uptake, modulate the innate immune system, and produce a wide variety of small-molecule metabolites that are detected by host receptor systems to regulate host metabolism and inflammatory pathways linked to CVD. 52,53 In addition to direct interactions, the gut microbiota can indirectly interact with the host via metabolites, which can appear in the circulation and in the urine.…”
Section: Role Of Microbiotamentioning
confidence: 99%
“…The gut microbiota is an important environmental factor and there is increasingly concrete evidence that the activity and composition of the gut microbiota are closely related to health. 52 , 53 …”
Section: Future Developmentsmentioning
confidence: 99%
See 1 more Smart Citation